ChemInform Abstract: Cooperative Catalysis: Combining an Achiral Metal Catalyst with a Chiral Broensted Acid Enables Highly Enantioselective Hydrogenation of Imines. Issue 13 (1st April 2014) - Tang, Weijun; Johnston, Steven; Li, Chaoqun; Iggo, Jonathan A.; Bacsa, John; Xiao, Jianliang
Abstract The catalytic system of title can be employed on imines derived from aromatic as well as aliphatic ketones.